If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 38 = 16 + x Reorder the terms: 38 + 3x = 16 + x Solving 38 + 3x = 16 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 38 + 3x + -1x = 16 + x + -1x Combine like terms: 3x + -1x = 2x 38 + 2x = 16 + x + -1x Combine like terms: x + -1x = 0 38 + 2x = 16 + 0 38 + 2x = 16 Add '-38' to each side of the equation. 38 + -38 + 2x = 16 + -38 Combine like terms: 38 + -38 = 0 0 + 2x = 16 + -38 2x = 16 + -38 Combine like terms: 16 + -38 = -22 2x = -22 Divide each side by '2'. x = -11 Simplifying x = -11
| 184+2h=986 | | x+3x-1+x+15= | | 3x^2-6x+11000=0 | | 4x(x)=49 | | 2x^6*x-95=0 | | 0.2p-10= | | 6-4x=x+7(x+8) | | 144=16t | | 28(p+30)=3,108 | | 8.32+7.76-10.09= | | 3,108=28(p+30) | | x+(3x+4)=112 | | 6(2x-3)=24 | | X+(x-21)=157 | | 2x+12+7x-1=x | | 2(3x+3)=11x+3-5x+3 | | z/(-1)=9 | | -8+x=46 | | X+X-21=157 | | 6.8/(-4)= | | 2x+11x=52+x | | x-(-5)=34 | | 9x+15=5x+1 | | 4*(-4.3)*-2= | | X^2-15x-11000=0 | | 4(x+8)=8x+3-4x+29 | | 4b+3-b=-7+2+b | | 6-3(4x+2)-10x= | | (-X+1)2+(-x-1)2=0 | | k+12/17=2 | | 8x+3=8x+3-4x+29 | | 80x^4-48x^2+4=0 |